(E)-1-Bromo-4-(2-nitroprop-1-enyl)benzene - Li, Bailin (International Union of Crystallography, 2009)
The title compound, C(9)H(8)BrNO(2), which was synthesized by the condensation of 4-bromobenzaldehyde with nitroethane, possesses a trans configuration. The dihedral angle between the benzene ring and the mean plane of the double bond is 7.31 (3)°. The crystal structure is stabilized by short intermolecular Br⋯O contacts [3.168 (4) Å].